2015
DOI: 10.1108/jpbafm-27-03-2015-b003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of board composition on public sector pension funding

Abstract: Public pension plans in the U.S. are seriously underfunded, especially following the financial market crisis of 2008-2009 which resulted in large investment losses. However, funding levels vary widely across plans. Pension boards of trustees make key management decisions in pension systems and these decisions have significant effects on funded levels, yet our empirical knowledge of board management is limited. This study explores the effect of board composition on pension funding levels. Existing theoretical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Furthermore, Chen et al (2015) argue that a pension board composition is associated with public pension funding levels. They find that an increase in political appointees and employee members on the board of the pension fund increases the financial performance of pension funds.…”
Section: Factors Behind Pension Underfundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Chen et al (2015) argue that a pension board composition is associated with public pension funding levels. They find that an increase in political appointees and employee members on the board of the pension fund increases the financial performance of pension funds.…”
Section: Factors Behind Pension Underfundingmentioning
confidence: 99%
“…How did state pension finances get so bad? Existing studies offer evidence of a mix of factors—generously defined pension benefit promises, poor actuarial estimates of retiree behavior and longevity, manipulations of accounting practices, excessive estimates of what pension fund balances could earn, and failure to make the necessary annual payments into the pension fund to support future benefits (Chen, 2018; Chen et al, 2015; Coggburn & Kearney, 2010; Novy-Marx & Rauh, 2011; Stalebrink, 2014). Because these factors may be manipulated by public officials for institutional and for private financial gain, it is useful to consider whether contexts with public corruption are at play and, hence, potentially exacerbate the underfunding of state pension plans (Andonov et al, 2018; H.…”
Section: Introductionmentioning
confidence: 99%
“…A benevolent board member would take actions that are of the most benefit to others, regardless of outside factors. An ongoing issue in government is that politicians are often viewed as continuously running for re-election, which can often influence their decisions (Chen et al , 2015). It is therefore conceivable that the GFO/board member relationship can suffer from this same view, where the GFO views board members as only caring about staying in office and not about what is in the best interest of the municipality (only what is popular).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…1. Homogeneity in actuarial assumptions is a strength of our study. The variability in optimistic actuarial assumptions is well-documented (Vermeer et al , 2010; Easterday and Eaton, 2012), and pension board governance has also been shown to influence assumptions (Chen et al , 2015). These concerns are mitigated in our sample with the use of governments from a multi-employer plan with homogeneity in actuarial assumptions.…”
Section: Notesmentioning
confidence: 99%